Association between thyroid cancer and cardiovascular disease: A meta-analysis - Tsai, Wen-Hsuan; Zeng, Yi-Hong; Lee, Chun-Chuan; Chien, Ming-Nan; Liu, Sung-Chen; Chien, Kuo-Liong; Cheng, Shih-Ping; Tseng, Po-Jung; Tsai, Ming-Chieh (Frontiers in Cardiovascular Medicine, 2023)
Objective To determine the association between thyroid cancer and coronary artery disease, atrial fibrillation, cerebrovascular disease, and cardiovascular disease mortality. Methods The PubMed, Embase, and Cochrane Library databases were searched for eligible studies from inception to September 22, 2022. Keywords included “thyroid cancer”, “atrial fibrillation”, “coronary artery disease”, “cerebrovascular disease”, and “mortality”. Primary outcomes included the incidence of coronary artery disease, cerebrovascular disease, atrial fibrillation, and cardiovascular disease mortality among patients with thyroid cancer. Secondary outcomes included cardiovascular disease events among those with thyroid cancer that received or did not receive radioactive iodine or lenvatinib. Estimates were pooled using fixed- and random-effects meta-analysis. Results A total of 771,220 patients who underwent thyroidectomy in 15 studies were included. Risk for cerebrovascular disease (risk ratio [RR] 1.15 [95% confidence interval (CI) 1.10–1.21]) and atrial fibrillation [RR 1.59 (95% CI: 1.45–1.73)] were significantly increased. Risk for coronary artery disease was significantly increased [RR 1.12 (95% CI: 1.08–1.17)] in the common effect model. Cardiovascular disease mortality associated with thyroid cancer was not significant [RR 0.93 (95% CI: 0.59–1.45)]. Radioactive iodine had a neutral effect on cardiovascular disease [RR 1.00 (95% CI: 0.87–1.16)], and there was no beneficial nor harmful effect among different RAI doses. Conclusions Thyroid cancer was significantly associated with a higher risk for cerebrovascular disease and atrial fibrillation; however, the hazard risk was not different between patients with and without radioactive iodine treatment. Thyroid cancer treatment should be individualized considering the potential harms and benefits to cardiovascular health.